2019
DOI: 10.1002/tox.22882
|View full text |Cite
|
Sign up to set email alerts
|

Deep sea minerals ameliorate diabetic‐induced inflammation via inhibition of TNFα signaling pathways

Abstract: It has been well‐documented that the consumption of deep sea water (DSW) has beneficial effects on myocardial hypertrophy and cardiac apoptosis induced by hypercholesterolemia. However, the molecular mechanisms for the anti‐inflammatory effects of DSW on diabetic cardiomyopathy are still largely unclear. The main purpose of this present study was to test the hypothesis that DSW exerts anti‐inflammatory effects through the suppression of the TNF‐α‐mediated signaling pathways. IP injection of streptozotocin (STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…The mitogen-activated protein kinase (MAPK) pathway has been linked to a number of pathogenic responses including inflammation and oxidative stress. Supporting evidences have shown that MAPK signaling pathways are critically involved in the pathogenesis of several diabetic complications ( Lu et al, 2020 ). Specifically, MAPK p38 pathway has been reported to be activated in diabetes ( Ma et al, 2015 ; Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) pathway has been linked to a number of pathogenic responses including inflammation and oxidative stress. Supporting evidences have shown that MAPK signaling pathways are critically involved in the pathogenesis of several diabetic complications ( Lu et al, 2020 ). Specifically, MAPK p38 pathway has been reported to be activated in diabetes ( Ma et al, 2015 ; Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…55 It has been believed that miR-124-mediated reductions in USP 2 and 14 led to enhanced ubiquitination of vesicle extracellular vesicles, resulting in vesicle fusion with lysosomes and TNF-degradation. 56 Because both C/EBP-α and TNF-α are M1 polarization transcription factors, we hypothesized that miR-124 reduced inflammation by inhibiting C/EBP-α, which in turn inhibited TNF-α. 57 Similarly, the delivery of L/ZnONPs resulted in MiR-124 activation and, consequently, suppression of inflammation and C/EBP mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐124 was found to reduce apoptosis and alleviate renal lesions in the diabetic nephropathy rat model 55 . It has been believed that miR‐124‐mediated reductions in USP 2 and 14 led to enhanced ubiquitination of vesicle extracellular vesicles, resulting in vesicle fusion with lysosomes and TNF‐degradation 56 . Because both C/EBP‐α and TNF‐α are M1 polarization transcription factors, we hypothesized that miR‐124 reduced inflammation by inhibiting C/EBP‐α, which in turn inhibited TNF‐α 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The AGE-RAGE signaling pathway reacts on cell activation and tissue damage and has the activity of promoting the expression and release of in ammatory factors [35]. The TNF and IL-17 signaling pathways also play a crucial part in the occurrence and development of in ammation [26,36,37].…”
Section: Discussionmentioning
confidence: 99%